2023
DOI: 10.1001/jamanetworkopen.2023.24369
|View full text |Cite
|
Sign up to set email alerts
|

Neurological and Psychological Sequelae Associated With Multisystem Inflammatory Syndrome in Children

Abstract: ImportanceAcute neurological involvement occurs in some patients with multisystem inflammatory syndrome in children (MIS-C), but few data report neurological and psychological sequelae, and no investigations include direct assessments of cognitive function 6 to 12 months after discharge.ObjectiveTo characterize neurological, psychological, and quality of life sequelae after MIS-C.Design, Setting, and ParticipantsThis cross-sectional cohort study was conducted in the US and Canada. Participants included childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Nearly 30% of parents reported their child as being not recovered at a median of 1.5 years following hospitalization. Published studies of COVID-19 Syndrome in children have reported prevalence rates of 1%-66%, with higher risk in children associated with age <5 years, adolescent age, and increased severity of illness (6,18,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Our study's finding that two-thirds of children were experiencing either new or continued symptoms is similar to previously published surveys (6).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Nearly 30% of parents reported their child as being not recovered at a median of 1.5 years following hospitalization. Published studies of COVID-19 Syndrome in children have reported prevalence rates of 1%-66%, with higher risk in children associated with age <5 years, adolescent age, and increased severity of illness (6,18,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Our study's finding that two-thirds of children were experiencing either new or continued symptoms is similar to previously published surveys (6).…”
Section: Discussionsupporting
confidence: 87%
“…Our study's finding that two-thirds of children were experiencing either new or continued symptoms is similar to previously published surveys ( 6 ). Prior work evaluating Post-COVID-19 Syndrome used various designs (e.g., single center ( 39 ), community ( 34 ), and national ( 30 , 38 , 41 , 42 ), definitions, data sources (e.g., proxy or child report surveys or in-person assessments ( 32 , 36 , 37 , 42 ), electronic health record ( 31 ), and insurance registries ( 18 ), ages (e.g., inclusive pediatric age range ( 37 ) vs. adolescents( 40 , 42 ), specific SARS-CoV-2-related condition ( 33 , 35 37 ), level of care, and time points, contributing to the wide-ranging prevalence estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is currently ample evidence that autoimmunity and immune hypofunction play an important role in many patients with long COVID. [ 50 53 ] This includes not only the occurrence of Multisystem Inflammatory Syndrome in Children [ 54 ] but also an increase in incidence of common infections such as respiratory syncytial virus (RSV) and streptococcal disease.…”
Section: Immune Hypofunction After Acute Covid-19mentioning
confidence: 99%